EVALUASI GEOTEKNIK DAN STRUKTUR PADA DERMAGA EKSISTING TERMINAL PETI KEMAS SEMARANG - Aditya Yoga Satria; Dhimas Noor Fattah; Indrastono Dwi Atmanto; Himawan Indarto (Jurnal Karya Teknik Sipil, 2013)
ABSTRACTOne of the Semarang Tanjung Emas flagship facility is a container terminal with field accumulation which is a container handling facility. When viewed from the tendency of the flow of goods through ports, each year has increased. However, an increase in loading and unloading activities are often disrupted by tidal water that flooded dock container terminals. Therefore, the needs of adding  elevation dock container terminals, so that loading and unloading activities are not disrupted. Prior to the adding elevation of the wharf, first geotechnical and structural must be evaluated. From the results of the analysis, geotechnical existing capable of withstanding the load adding elevation dock. Consolidation settlement on geotechnical dock container Semarang is 11 cm, with the consolidation time is 16 months. So the plan elevation of 1.5 m must be added by 11 cm. The decrease was due to land subsidence 11cm/year, so plan elevation of 1.5 m can extend the life of the wharf service to 13 years and 10 months. For existing dock structure able to withstand loads due to the adding elevation of the wharf so it is not necessary to adding capacity. So that the evaluation can be continued into the planning for the elevation of the wharf form of additional beams and plates were riveted by the column.